Association between bullying at school and tooth loss among 15-19-year-olds from southern Brazil - Giovanna Leal KLEIN; Letícia Donato COMIM; Ângela DALLA NORA; Débora Nunes de Oliveira RACKI; Julio Eduardo do Amaral ZENKNER; Luana Severo ALVES (Sociedade Brasileira de Pesquisa Odontológica, 2024)
Abstract This study aimed to investigate the association between bullying at school and tooth loss in southern Brazilian adolescents. This population-based cross-sectional study included a representative sample of 15-19-year-old students attending high schools in Santa Maria, southern Brazil. Data on sociodemographic and behavioral variables were collected through questionnaires. Contextual data on bullying at school was provided by educational institutions (bullying episodes in the previous year: 'no,' 'sometimes,' or 'often'). Tooth loss was clinically assessed by the M component of the DMFT index, modeled as a discrete variable. Multilevel Poisson regression was used, and rate ratios (RR) and 95% confidence intervals (CI) were estimated. The prevalence of tooth loss was 9.2% (95%CI = 7.5-10.8). Adolescents who attended the schools where bullying events often occurred had 0.39 (95%CI = 0.33-0.45) missing teeth, on average, in contrast to an average of 0.14 (95%CI = 0.08-0.19) among those whose schools did not experience bullying in the previous year. After adjusting for important cofactors, the contextual variable of bullying at school remained significantly associated with the study outcome. Adolescents who attended schools where bullying frequently occurred were 2.49-fold more likely to have an additional missing tooth than those whose school did not experience bullying in the previous year (RR = 2.49, 95%CI = 1.37-4.51, p = 0.003). In conclusion, the frequent bullying episodes at school were associated with more permanent teeth lost due to caries in this population. Hence, improving the school environment may improve the oral health of adolescents.